The origin of the Slavic pronouns kolě and koli. A contribution to the history of relative clauses in Slavic languages from a typological perspective - Ostrowski, Norbert (Papers in Linguistics, 2026)
This article analyses the origin of Old Church Slavonic dokolě [how long] and koli [when, whenever]. Its aim is to determine the possible syntactic context in which ko-lě and ko-li could be combined; *ko- continues the nom.-acc. of Indo-European indefinite pronoun *kwod. Such a context was found in universal concessive conditionals, which are the most common source of indefinite pronouns in the “free choice determiner” function, e.g. Załóż cokolwiek = co chcesz [Wear anything = whatever you want]. Universal concessive conditionals continue Indo-European correlative structures of relative clauses, a type widely attested in old IE languages, e.g. Hittite and Old Indic, and only residually attested in Balto-Slavic languages, e.g. Polish Jaki ojciec, taki syn [Like father, like son]. The older layer of Balto-Slavic relative clauses is represented by sentences with IE relative pronoun *yo-, e.g. je-lě and je-li, where *je- continues the nom.-acc. of IE relative pronoun *yod. Universal concessive conditionals were also a context that favoured the spread of the indefinite pronoun *kwo- at the expense of the Balto-Slavic relative pronoun *yo-, leading to the occurrence of the pairs ko-lě : je-lě and ko-li : je-li. Further research is needed to provide a precise description of the development of relative clauses in Balto-Slavic languages. The present article is a preliminary contribution to etymological research that takes into account syntax and typology, which are usually underestimated by etymologists.